Desempenho diagnóstico e avaliação da eficácia protetora de proteínas recombinantes de Leishmania spp. e de uma quimera polipeptídica contra as leishmanioses tegumentar e visceral - Daniel Silva Dias (2018)
Protection against reinfection by Leishmania spp. species indicates the possibility of developing a prophylactic vaccine against leishmaniasis. The advancement of biotechnology tools has been showing to be a good prospect for the development of new products. In the present work, three proteins: a protein containing glutamine-rich tetratricopeptide repetitions (SGT), a hypothetical protein (LiHyS) and prohibitin (PHB), which were identified in a previous study using an immunoproteomic technique, in their recombinant form, were used as serological markers for leishmaniasis. The immunogenicity of the proteins was also evaluated in their recombinant forms isolated or in association, as well as a protein chimera composed of the major T-cell epitopes of the molecules. All associated with saponin as adjuvant and administered in BALB/c mice. Vaccine efficacy was evaluated against challenge infection with L. infantum. The results showed that the animals vaccinated with the proteins presented a high production of IFN-, IL-12 and GM-CSF, allied to a low production of IL-4 and IL-10, when compared to the control groups. Also, the animals showed a significant reduction in the parasite load in all organs analyzed. The protection was related to a high production of IFN-, which occurred mainly through CD4+ T cells. Interestingly, the chimera presented a greater protection effectiveness and immunogenicity when compared to the use of proteins alone or in combination. As for the serological tests, the recombinant proteins also presented higher sensitivity and specificity values for the diagnosis of visceral leishmaniasis when compared to controls using the rA2 antigen and an antigen preparation of Leishmania. Thus, the present work presents novel proteins and a recombinant chimera that can be used as vaccine candidates against visceral leishmaniasis, as well as serological markers for detection of the disease in infected mammalian hosts.